The Influence of Data Quality and Machine Learning Algorithms on AI Prediction Performance in Business Analysis in Indonesia - Judijanto, Loso; Muda Priyangan, Donny; Muthmainah, Hanifah Nurul; Jata, I Wayan (Eastasouth Institute, 2023)
This research investigates the intricate relationships among AI prediction performance, business analysis, data quality, and machine learning algorithms within the manufacturing sector in Indonesia. Through structural equation modeling analysis, the study explores the impact of these variables on one another, shedding light on the dynamics that contribute to successful AI adoption and business decision-making. The findings underscore the pivotal role of data quality in influencing AI prediction performance and machine learning algorithms, ultimately shaping the effectiveness of business analysis. The results provide practical insights for manufacturing companies seeking to optimize their data management practices and harness the potential of advanced technologies for strategic decision-making.